Interpreting the play script : contemplation and analysis - Fliotsos, Anne L., 1964- (Palgrave Macmillan, 2011)
"The starting point for virtually all theatre is studying the play script, but what does this involve? Interpreting the Play Script: Contemplation and Analysis argues that one type of analysis cannot fit every play, nor does one method suit every theatre artist or collaborative team. The first text to combine traditional and non-traditional models, it gives students a range of tools with which to approach different kinds of performance. Supported by pragmatic questions, practical exercises and sources for further reading, this book will challenge students and theatre practitioners to engage with the play using both analysis and contemplation. It is essential reading for anyone wanting to unlock and more fully understand the performance potential of any play"--